Perspective of Village Government Capacity in Village Development in Jember District - HELPIASTUTI, SELFI BUDI (Advances in Social Sciences Research Journal, 2017)
The implementation of village development requires the capacity of the village government in the form of: regulatory capacity, extraction capacity, distributive capacity, responsive capacity and network capacity. Village capacity will help village governments to implement village infrastructure development in accordance with village development implementation guidelines. Type of research used in this research is descriptive type research with qualitative approach. Informants in this research are village head, village secretary, village treasurer, head of Village councils, head of hamlet, village facilitator, and community figure who know related to village development implementation activity. The result of the research shows the regulation capacity in the form village regulations of Village budget, village regulations of village government work plan, and village head's decision on implementation team. Extraction capacity is the extraction of human assets by the absorption of 40 original workers of the village, and the extraction of social assets in the form of community participation. Distributive capacity of the implementation authority of development there is a problem of basic tasks and functions and for the distribution of development is in accordance with the needs of the community. Responsive capacity is a verbal response by the village government over community complaints. The network capacity is in the form of cooperation between the village government and the Public Works Department, and the provider of goods and services, but the cooperation is only limited to administrative documents.